Potential Risk Factors for Autism in Children Requiring Neonatal Intensive Care Unit - Matos, Marília Barbosa de; Bara, Tiago S.; Felden, Érico P. G.; Cordeiro, Mara L. (Neuropediatrics, 2021)
Background The etiology of autism spectrum disorder (ASD) is complex and involves the interplay of genetic and environmental factors.Aim We sought to identify potential prenatal, perinatal, and neonatal risk factors for ASD in a unique population of children who had perinatal complications and required care in a neonatal intensive care unit (NICU).Methods This prospective cohort study included 73 patients discharged from a NICU who received long-term follow-up at the largest children's hospital in Brazil. Potential risk factors were compared between 44 children with a diagnosis of ASD and 29 children without using the Mann–Whitney U test. Proportions were analyzed using the chi-square test. Simple and multiple logistic regression tests were performed.Results Of 38 factors analyzed, the following 7 were associated with ASD: family history of neuropsychiatric disorders (p = 0.049); maternal psychological distress during pregnancy (p = 0.007); ≥ 26 days in the NICU (p = 0.001); feeding tube for ≥ 15 days (p = 0.014); retinopathy of prematurity (p = 0.022); use of three or more antibiotics (p = 0.008); and co-sleeping until up to 2 years of age (p = 0.004).Conclusion This study found associations between specific risk factors during critical neurodevelopmental periods and a subsequent diagnosis of ASD. Knowledge of the etiologic factors that may influence the development for ASD is paramount for the development of intervention strategies and improvement of prognoses.
Keywords: autism; Brazil; intensive care; neonatal; risk factors